Biological analysis method based on the relationship between athlete’s PSI rhythm and sports injury - Zhang, Zhongxing; Cai, Jun (Molecular & cellular biomechanics, 2024)
Biorhythm is the law of cyclical changes in individual life activity characteristics as time changes. Biorhythm is an internal law of a biological organism, which comes from the changes that a biological organism is affected by changes in the external environment during natural activities, so its change law is similar to the cycle of the natural environment. Biological rhythms play an important role in mediating human body functions, vital activities, body temperature and other physiological reactions. The balance and stability of biological rhythms can ensure the healthy life activities of the human body. Disrupting the balance of biological rhythms may cause various kinds of human body. In this paper, the research of biological analysis method based on the relationship between athlete’s PSI (Physical, Sensitive, Intellectual) rhythm and sports injury is mainly introduced, and ideas and directions are intended to be provided for analyzing the relationship between athlete’s physical strength, emotion, intelligence and sports injury. This paper proposes a research strategy based on the biological analysis method of athlete’s PSI rhythm and sports injury, including measurement of biological rhythm, literature retrieval method, expert interview method, questionnaire survey method, clustering algorithm-based biological analysis method. A research experiment on the biological analysis method of the relationship between PSI rhythm and sports injury is conducted. The experimental results of this paper indicated that most sports injuries of athletes occur in the critical period of PSI rhythm, with an average incidence of 70.14%. Athletes’ training and competition can be avoided in this critical period as much as possible.